2019
DOI: 10.1186/s12998-019-0263-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing attitudes of patient-centred care among students in international chiropractic educational programs: a cross-sectional survey

Abstract: Background Patient-centred care is internationally recognized as a foundation of quality patient care. Attitudes of students towards patient-centred care have been assessed in various health professions. However, little is known how chiropractic students’ attitudes towards patient-centred care compare to those of other health professions or whether they vary internationally, and between academic programs. Objective To assess the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(57 reference statements)
2
11
2
Order By: Relevance
“…The findings related to PPOS scores were essentially consistent with previous Chinese-based and studies based in some Eastern and Western countries [ 22 , 23 , 24 , 25 , 26 ]. The findings reported that physicians rated relatively high caring and low sharing scores, which indicates a similar pattern that physicians were more patient-centered in the caring subscale than in the sharing subscale [ 22 , 23 , 24 , 25 ]. However, the differences between caring and sharing scores were much higher than the results reported by other researches, with much less patient involvement in information and decision-making.…”
Section: Discussionsupporting
confidence: 90%
“…The findings related to PPOS scores were essentially consistent with previous Chinese-based and studies based in some Eastern and Western countries [ 22 , 23 , 24 , 25 , 26 ]. The findings reported that physicians rated relatively high caring and low sharing scores, which indicates a similar pattern that physicians were more patient-centered in the caring subscale than in the sharing subscale [ 22 , 23 , 24 , 25 ]. However, the differences between caring and sharing scores were much higher than the results reported by other researches, with much less patient involvement in information and decision-making.…”
Section: Discussionsupporting
confidence: 90%
“…The PPOS was the instrument of choice as it has been shown previously to be valid 46 and reliable. 29,31,34 However, contrary to these previous studies, this current study did not show the PPOS to be a reliable instrument, in the context of the study. Although reliability was limited, certain relevant trends were observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Female students generally have higher average scores than male students, [27][28][29][30][31] and some studies conclude that increasing age influences scores, 29 whereas year of study has shown, in some studies, to have no effect on average scores. 28,[32][33][34] In South Africa, there are 2 university-based chiropractic educational programs that are accredited by the Council for Higher Education and registered with the South African Qualifications Authority. 35 Both these institutions hold international accreditation with the European Council on Chiropractic Education, 36 obtained in 2009 and 2010, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recognition of patient-centeredness as the foundation for quality of patient care [30][31][32], it is often overlooked in patient safety surveys [22,[33][34][35]. A recent pilot project assessing patient-centered attitudes conducted at some of the same chiropractic programs included in our study, revealed a lesser focus on patient-centered care than similar studies with medical students [36,37]. This suggests chiropractic curricular content (and hidden/null curriculum content) likely influences students' attitudes toward patientcentered care.…”
Section: Discussionmentioning
confidence: 76%